Optimization of the Substitution Pattern of 1, 3‐Disubstituted Imidazo[1, 5‐a]Pyridines and ‐Quinolines for Electro‐Optical Applications. Issue 5 (28th January 2020) - Albrecht, Georg; Rössiger, Carina; Herr, Jasmin Martha; Locke, Harald; Yanagi, Hisao; Göttlich, Richard; Schlettwein, Derck
Abstract : A series of recently synthesized 1, 3‐disubstituted imidazo[1, 5‐ a ]pyridines (IPs) and ‐quinolines (IQs) targeting at increased efficiency of luminescence is investigated. The properties of molecules in solution as well as their change in the solid state are reported and assessed regarding possible application in organic electronics. The influence of increased ring size by substitution, e.g., exchanging phenyl to naphthalenyl, as well as pyridyl to quinolinyl moieties, and by means of a larger IQ fluorophore is discussed. A higher oscillator strength and quantum yield can be achieved. Frontier orbital energies are estimated based on cyclic voltammetry and density functional theory (DFT) calculations. Single crystals of molecules are grown. A red‐shift in the photoluminescence spectra found for crystals of IQs compared with those in solution is proposed to be caused by intermolecular coupling based on the parallel stacking of the enlarged fluorophore units. Thin films deposited by physical vapor deposition exhibit similar effects, showing promise as active layers in organic light‐emitting diodes (OLEDs). An amorphous morphology is inferred for these films from both spectral broadening in photoluminescence and atomic force microscopy. An OLED test structure is prepared, using the most efficient IQ lumophore and demonstrating the feasibility of obtaining electroluminescence from such thin films. Abstract : A series of substituted imidazopyridines and imidazoquinolines is studied. The changes of molecular properties as a consequence of molecular packing in single crystals and thin films are analyzed and discussed regarding possible application in organic electronics. Strategies toward higher luminescence intensities are presented. An organic light‐emitting diode (OLED) test structure is prepared, demonstrating the feasibility of the present approach.